Rancang Bangun Sistem Informasi KKN LPPM UPN “Veteran” Jawa Timur Berbasis Web Menggunakan Metode Rapid Application Developmet - Anggoro, M. Novianto; Wibowo, Nur Cahyo; Kartika, Dhian Satria Yudha (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UPN “Veteran” Jawa Timur plays an active role in organizing research and community service activities. One of its main programs is the Kuliah Kerja Nyata (KKN). Currently, the management of KKN activities lacks a system that supports the business processes involved. The registration and submission of outputs are still done using Google Forms, and there is no system for digitizing certificates. Therefore, the "Sistem Informasi KKN (SISKA)" was developed using the Rapid Application Development (RAD) approach. The goal of developing the Sistem Informasi KKN (SISKA) is to streamline the administrative processes that previously consumed significant time and human resources, allowing a greater focus on the core aspects of the KKN program. This system benefits LPPM UPN "Veteran" Jawa Timur, field supervisors, and students. The User Acceptance Test (UAT) results showed a score of 84.375%, indicating that users strongly agree that the KKN information system meets their needs.